2017
DOI: 10.1007/978-981-10-6020-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation in Treatment of Breast Cancer

Abstract: Cell cycle progression and cell proliferation are under precise and orchestrated control in normal cells. However, uncontrolled cell proliferation caused by aberrant cell cycle progression is a crucial characteristic of cancer. Understanding cell cycle progression and its regulation sheds light on cancer treatment. Agents targeting cell cycle regulators (such as CDKs) have been considered as promising candidates in cancer treatment. Although the first-generation pan-CDK inhibitors failed in clinical trials bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 129 publications
3
23
0
Order By: Relevance
“…Consistent with the results of a previous study, the present results indicated that cell cycle progression and the AKT signaling pathway were significantly dysregulated in patients with breast cancer (28). The EGFR downstream AKT/Skp2associated pathway has a crucial role in regulating the cell cycle and cell proliferation in tumorigenesis (29).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the results of a previous study, the present results indicated that cell cycle progression and the AKT signaling pathway were significantly dysregulated in patients with breast cancer (28). The EGFR downstream AKT/Skp2associated pathway has a crucial role in regulating the cell cycle and cell proliferation in tumorigenesis (29).…”
Section: Discussionsupporting
confidence: 92%
“…Cell cycle control is a highly regulated process that involves a complex cascade of events. Modulation of the expression and function of cell cycle regulatory proteins provides an important approach for the inhibition of tumor growth (Cai and Liu, 2017). Our results showed that Cyclins (cyclin A2, B1, B2), CDK2, CDC2 were down-regulated in BTPs treated HepG2 cells, while CDK inhibitor p21WAF1 and other growth inhibitors BTG2 and VDUP1 were upregulated, suggesting that BTPs inhibit the growth of HepG 2 cells through the arrest of cell cycle and the inhibition of cell proliferation.…”
Section: Conflict Of Interestmentioning
confidence: 67%
“…Considering the role of TGF-beta signaling pathways in tumors, it is inferred that SYNJ2 and its co-expressed genes can promote LUAD cells' in ltration and migration by TGF-beta signaling pathways. Since cancer is characterized by the deregulation of cell cycle activity that lead to aberrant cell proliferation [32][33], many authors have concluded that cancer can be regarded as a disease of the cell cycle [34]. Previous studies reported that many genes can regulate cell cycles to promote LC cell proliferations [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%